Bimodal Functionality in a Porous Covalent Triazine Framework by Rational Integration of an Electron‐Rich and ‐Deficient Pore Surface. Issue 14 (18th February 2016) - Karmakar, Avishek; Kumar, Amrit; Chaudhari, Abhijeet K.; Samanta, Partha; Desai, Aamod V.; Krishna, Rajamani; Ghosh, Sujit K.
Abstract: A porous covalent triazine framework (CTF) consisting of both an electron‐deficient central triazine core and electron‐rich aromatic building blocks is reported. Taking advantage of the dual nature of the pore surface, bimodal functionality has been achieved. The electron deficiency in the central core has been utilized to address one of the pertinent problems in chemical industries, namely separation of benzene from its cyclic saturated congener, that is, cyclohexane. Also, by virtue of the electron‐rich aromatic rings with Lewis basic sites, aqueous‐phase chemical sensing of a nitroaromatic compound of highly explosive nature (2, 4, 6‐trinitrophenol; TNP) has been achieved. The present compound supersedes the performance of previously reported COFs in both the aspects. Notably, this reports the first example of pore‐surface engineering leading to bimodal functionality in CTFs. Abstract : Best of both worlds : A porous covalent triazine framework consisting of both an electron‐deficient central triazine core and electron‐rich aromatic building blocks is reported. The electron deficiency in the central core was utilized to separate benzene from cyclohexane. By virtue of the electron‐rich aromatic rings with Lewis basic sites, aqueous phase chemical sensing of highly explosive 2, 4, 6‐trinitrophenol was achieved.